800 CHAPTER 39. STATISTICAL TESTS

Thus the first term in 39.2 is the moment generating function of X̄ . Some computationsshow that the second term is the moment generating function of the vector(

X1− X̄ · · · Xn− X̄)

Indeed,

E

(exp

n

∑k=1

tk (Xk− X̄)

)= E

(exp

(∑k

tkXk−∑k

tk1n ∑

jX j

))

= E

(exp

(∑k

tkXk−∑j

t j1n ∑

kXk

))= E

(exp

(∑

j∑k

tk− t j

nXk

))

= ∏j

E

(exp

(∑k

tk− t j

nXk

))= ∏

j∏

kE(

exp(

tk− t j

nXk

))

= ∏j

∏k

(exp

((tk− t j

)+

12

(tk− t j

n

)2

σ2

))

= exp

(∑

j∑k

12

(tk− t j

n

)2

σ2

)

Therefore, by Proposition 38.9.7, X̄ and this random vector are linearly independent. ■The above proposition leads to something interesting, the distribution of nS2/σ2. Let

the Xk be independent and normally distributed with mean µ and variance σ2. Then

S2 ≡ 1n

n

∑k=1

(Xk− X̄)2

The distribution of nS2/σ2 = ∑nk=1

(Xk−X̄)2

σ2 will be considered. If we know this, then sinceS2 is experimentally determined, it will follow that we could estimate σ2. First note that

Xk− X̄ = Xk−µ +µ− X̄

and so(Xk− X̄)

2= (Xk−µ)2−2(Xk−µ)(X̄−µ)+(X̄−µ)

2

2n

∑k=1

(Xk−µ)(X̄−µ) = 2n(X̄−µ)(X̄−µ)

Therefore,n

∑k=1

(Xk− X̄)2+n(X̄−µ)

2=

n

∑k=1

(Xk−µ)2

Thenn

∑k=1

(Xk− X̄)2

σ2 +n(X̄−µ)

2

σ2 =n

∑k=1

(Xk−µ)2

σ2

800 CHAPTER 39. STATISTICAL TESTSThus the first term in 39.2 is the moment generating function of X. Some computationsshow that the second term is the moment generating function of the vector( xi-¥ . X,-¥ )Indeed,E [oo y tk (X, -»)) =E (os (Ena _ EutDss) )k=1 k k jenfps-ptee)}-el(e8'2))(gs) (ol)nM [ow ((‘ iy) +vo(EEa(S4) ©)Therefore, by Proposition 38.9.7, X and this random vector are linearly independent. MlThe above proposition leads to something interesting, the distribution of nS*/o*. Letthe X, be independent and normally distributed with mean 1 and variance 07. ThenNile——_=|a—QNNNYY1=i hl X, —X—7\2The distribution of nS?/o? = Y7_, Mar will be considered. If we know this, then sinceS* is experimentally determined, it will follow that we could estimate o7. First note thatX,-X =X,-u+pu—-Xand so(Xp —X)° = (Xp — bw)? — 2 (Xe — mw) (X — mw) + (KX -p)”2¥ (X—m) (Rm) =2n(X —w) (F —p)k=1Therefore, , ,Yi (% —X) +0 (® — uw) = Y (Xb)?k=1 k=1Then